Ukraine : 2008 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Ukraine. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation highlights that rapid domestic demand growth in Ukraine pushed the economy beyond its capacity in 2007-08, leading to accelerating inflation. The demand expansion, fed by fiscal and income policies and a capital-inflow driven surge in money and credit growth, in combination with rising food and energy prices, gradually lifted CPI inflation to more than 30 percent by end-April 2008. Executive Directors have commended Ukraine's continued strong economic growth and increased overall resilience to shocks. They have also expressed concern that some macroeconomic vulnerabilities have increased.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet